2010
DOI: 10.3727/096368910x506845
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mononuclear Cell Therapy Led to Alveolar-Capillary Membrane Repair, Improving Lung Mechanics in Endotoxin-Induced Acute Lung Injury

Abstract: The aim of this study was to test the hypothesis that bone marrow mononuclear cell (BMDMC) therapy led an improvement in lung mechanics and histology in endotoxin-induced lung injury. Twenty-four C57BL/6 mice were randomly divided into four groups (n = 6 each). In the acute lung injury (ALI) group, Escherichia coli lipopolysaccharide (LPS) was instilled intratracheally (40 μg, IT), and control (C) mice received saline (0.05 ml, IT). One hour after the administration of saline or LPS, BMDMC (2 × 10(7) cells) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Similar results were achieved when only conditioned medium of such cells was administrated [53]. Moreover, some reports in animal models have described that intrapulmonary MSC administration improved survival and reduced pulmonary edema formation [54], as well as promoted repair of epithelium and endothelium, with improvement in lung mechanics [55]. A recent study has observed that BMDMC therapy was effective in modulating the inflammatory and fibrogenic processes in models of pulmonary and extrapulmonary ALI induced by LPS; however, survival, lung mechanics, and histology improved more in extrapulmonary ALI.…”
Section: Stem Cells In Acute Lung Injury/acute Respiratory Distress Ssupporting
confidence: 68%
“…Similar results were achieved when only conditioned medium of such cells was administrated [53]. Moreover, some reports in animal models have described that intrapulmonary MSC administration improved survival and reduced pulmonary edema formation [54], as well as promoted repair of epithelium and endothelium, with improvement in lung mechanics [55]. A recent study has observed that BMDMC therapy was effective in modulating the inflammatory and fibrogenic processes in models of pulmonary and extrapulmonary ALI induced by LPS; however, survival, lung mechanics, and histology improved more in extrapulmonary ALI.…”
Section: Stem Cells In Acute Lung Injury/acute Respiratory Distress Ssupporting
confidence: 68%
“…Indeed, Prota and colleagues (57) assessed therapeutic efficacy at 28 days after LPS administration and Yamada and colleagues at 1 week after LPS instillation (58). We speculate that the acute phase of inflammation driven by monocytes may be detrimental to the host and that late-phase mononuclear cell recruitment may be beneficial.…”
Section: Discussionmentioning
confidence: 82%
“…In that regard, regulatory T lymphocytes (59) have been shown to be critical in the resolution of LPS-induced ALI through promoting neutrophil apoptosis. As such, the beneficial effects of MNC therapy in studies by Yamada and colleagues (58) and Prota and colleagues (57) may have been mediated via lymphocytes rather than monocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Transplantation of bone marrow-derived MSCs or EPCs has been reported to reduce mortality and ALI induced by endotoxin or sepsis in rodent models [Yamada et al, 2004;Gupta et al, 2007;Mei et al, 2007;Xu et al, 2007bXu et al, , 2008Nemeth et al, 2009;Araujo et al, 2010;Mao et al, 2010;Mei et al, 2010;Danchuk et al, 2011]. Although it has been shown that transplantation of bone marrow-derived mononuclear cells (BM-MNCs) in a model of LPSinduced ALI led to a repair of alveolar endothelium and epithelium and improvement in lung mechanics [Prota et al, 2010], studies focused on MSCs show that the mechanism of action of bone marrow-derived stem cells is predominantly paracrine [Lee et al, 2011a], with the release of molecules that have not only immunomodulatory effects but also act as growth factors, factors regulating endothelial and epithelial permeability and antimicrobial peptides that can potentially treat the major abnormalities underlying ALI, including impaired airway fluid clearance, altered lung endothelial permeability, dysregulated inflammation and infection ( fig. 2 ).…”
Section: Acute Lung Injurymentioning
confidence: 99%